Hubungan Antara Pola Makan Dengan Frekuensi Peningkatan Gula Darah Pada Penderita Diabetes Melitus - Jayadi, Alpian (Sekolah Tinggi Ilmu Kesehatan Surabaya, 2018)
A diet excessive and exceeds the number of calories the body can trigger the onset of diabetes mellitus is a chronic disease characterized by elevated blood sugar. The purpose of this study was to prove a link between diet and increased frequency of blood sugar in people with diabetes at the health center Medokan Ayu Surabaya. The method used in this study is the survey by Retro analytic perspective. Population of all diabetic patients who visited the health center in Surabaya Ayu Medokan by 47 people. Large sample of 32 respondents in the sample selection is simple random sampling. Instrument used questionnaires to diet while increasing the frequency of blood sugar using a recapitulation of the patient's status. Analysis using the Lambda test with significance level a = 0.05. The results obtained mostly good diet categories, namely (62.5%), whereas the frequency of elevated blood sugar more stout that is not repetitive (65.6%). The results obtained from the Lambda test p = 0.001. The conclusions of this study there is a relationship between diet and increased frequency of blood sugar in people with diabetes at the health center Ayu Medokan Surabaya, therefore, necessary to maintain the habit of DM patients with a good diet so that blood sugar can be controlled.